Coastal Processes and Longshore Sediment Transport along Krui Coast, Pesisir Barat of Lampung - Trika Agnestasia Tarigan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Longshore sediment transport is one of the main factors influencing coastal geomorphology along the Krui Coast, Pesisir Barat of Lampung. Longshore sediment transport is closely related to the longshore current that is generated when waves break obliquely to the coast. The growth of waves depends upon wind velocity, the duration of the wind, and the distance over which the wind blow called fetch. The daily data of wind speed and direction are forecast from European Centre for Medium-Range Weather Forecasts (ECMWF). This study examines for predicting longshore sediment transport rate using empirical method. The wave height and period were calculated using Shore Protection Manual (SPM) 1984 method and the longshore sediment transport estimation based on the CERC formula, which also includes the wave period, beach slope, sediment grain size, and breaking waves type. Based on the use CERC formula it is known that from the Southeast direction (Qlst(1) ) the sediment transport discharge is 2.394 m3/s, in 1 (one) year the amount of sediment transport reaches 75,495,718 m3/s. Whereas from the northwest direction of (Qlst(2)) the sediment transport debit is 2.472 m3/s, in 1 (one) year the amount of sediment transport reaches 77,951,925 m3/s.